(untitled) (Advancements in Homeopathic Research, 2022)
Someone has rightly said that our real-life partner is our own body, which has to support us and last us our lifetime. Being a sportsperson since the age of six, I have realized that my body is my temple that I need to worship and keep it healthy. Nutrition and Exercise are two important pillars towards the same.While there is lot of research work on the exercise regime one should follow in order to build balance, flexibility, strength, and endurance, not much is said about the significant part that the nutrition can play to achieve this objective and how good nutritional habits should start very early in life.I play competitive golf and I have realized over the years how critical good health is. My tournaments run for 5-6 hours every day for 4 days at a stretch with no relief, and sometimes we play 2-3 tours in a row with no gap. I need to have the same agility and energy on the fourth and final day of the tournament as I have on the first day. Many a player suffer on the last day not because they don’t have the talent, but because they lose their stamina by not paying attention to their diet.